Addressing food insecurity in sub-Saharan Africa: the role of cash transfers - Francesco Burchi; Margherita Scarlato; Giorgio D'Agostino (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Food insecurity, a complex and multi-faceted phenomenon, is currently one of the inter-national community's main priorities, especially in sub-Saharan Africa (SSA). As food insecurity in this region is most widespread in pockets of extreme poverty, particularly in rural areas, traditional agricultural or general economic interventions alone are unlikely to generate substantial improvements. Instead, there is ample scope for social protection schemes. This paper investigates the role played by rapidly expanding cash transfers (CTs) in enhancing food security. First, it offers an innovative conceptual framework for explaining the channels through which CT programmes can affect the various aspects of food security. It also illustrates how specific design features of CT programmes may generate effects through little known pathways, such as women's empowerment and improved intra-household decision-making. Second, based on this conceptual framework, the paper provides a systematic review of evidence of the effects of CT programmes on different aspects of food security in middle-income and low-income countries in SSA. A rigorous overview based on a comprehensive conceptual framework is missing from the literature, as most of the overview papers published to date have concentrated on the specific effects of CT programmes on monetary poverty, human capital accumulation or food expenditure. The paper shows that CTs offer great potential for enhancing households' access to food, as long as they take full account of: the targeting of beneficiaries; the regularity of payments; the size of monetary transfers; the need to amass political support. In order to enhance all the different aspects of food security in the medium to long-term, CTs should be integrated with other interventions such as public works programmes, nutritional education, nutritional supplements for vulnerable groups, and economic policies. This is the main rationale behind the planned new phase of the Productive Safety Net Programme (PSNP) in Ethiopia. Francesco Burchi is researcher at the German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE); Margherita Scarlato and Giorgio d'Agostino are researchers at the Department of Economics at Roma Tre University. Francesco Burchi is researcher at the German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE); Margherita Scarlato and Giorgio d'Agostino are researchers at the Department of Economics at Roma Tre University.
Keywords: 330; Armut und Ungleichheit; Soziale Sicherung und Inklusion